Predictors of dermatophyte infections among patients attending dermatology department in a government hospital in Setif Province, Algeria - Belmiloud, Boualem (2020)
Dermatophytes are fungi that break down keratin of the stratum corneum and grow. They cause superficial infections of the skin, hair, and nail that are referred to as tinea infections. This disease of major public health problem around the globe causing a considerable morbidity. Out of about 40.4 million inhabitants of Algeria, at least 568,900 (1.41%) of them have a serious fungal infection each year. However, determining of existence of dermatophyte infection would therefore help in deciding the actual prevalence rates of the infection and the risk factors associated. The results obtained in this study may be used as a baseline data for epidemiological studies of dermatophyte infection in the country. Also, the outcome may help policy makers to strengthen and prioritize primary prevention and control programs on dermatophyte infection Objectives: to determine the prevalence of dermatophyte infection and factors associated among patients attending Dermatologic Department in a government hospital in Setif province, Algeria. Methods: This was a cross sectional study done on patients attending Dermatologic department. Data had been collected using self-administered structured questionnaire with open and closed ended questions. The pilot study was conducted using 400 questionnaires to collect information on socio-demographic data, environment and sanitation, knowledge, attitude, and hygiene practice. Data was analyzed using IBM SPSS version 25. Results: The response rate was 78.75%. The overall mean age of the 315 respondents was 38.81± 16.37years. The mean family monthly income was DR 41163.49± 15370.2. Prevalence of dermatophyte infections found to be 33.7%, 26% of them had single infections. The multiple logistic regression analysis showed that patients with low family monthly income increased the odds of having dermatophyte infection with almost 3.23 times (COR=3.23, 95CI=.994-10.49, p=.05). Similarly, presence of chronic disease increased the odds of having dermatophyte infection with 2.27 times among patients with skin disease (COR=2.27, 95%CI=1.018-10.49, p=.045). Poor attitudes towards prevention of dermatophyte infection increased the odds of having dermatophyte infection by 2.58 times (COR=2.58, 95%CI=1.14-4.74, p=.002)and Patients who usually using public bath (hammam) are 4.81 times)more likely to have the disease(COR=4.81, 95%CI=2.59-8.93, p=.001). Conclusions: Dermatophyte infection is still present a problem of concern in Setif province, Algeria. Current control measures should be reassessed to enable introduction of effective measures to reduce dermatophyte infection especially among patients with chronic disease.